REAL-TIME GIS FOR MONITORING AND SECURITY: REAL-TIME GIS FOR MONITORING AND SECURITY - Dimanova, Donika; Y. Kuzmanov, Zdravko (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
Applications of geographic information systems in the security domain are diverse and cover various aspects such as crisis prevention and management, public safety, national security, critical infrastructure protection and military applications. Real-time GIS is essential for effective emergency response and management because it provides accurate information on the location and dynamics of events.